2022
DOI: 10.3390/molecules27113615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soaking Conditions and Fuzzy Analytical Method for Producing the Quick-Cooking Black Jasmine Rice

Abstract: The quick-cooking rice product is an interesting product for the market which is easy to cook, with good sensorial qualities and health benefits. This work aimed to study the effect of the soaking conditions, namely baking powder concentration (0.1, 0.2, or 0.3%), soaking temperature (room temperature, 50 or 60 °C), and soaking time (10, 20, or 30 min), in order to improve the physical properties and also the sensory characteristics, with high bioactive compound content, of Quick-Cooking Black Jasmine Rice (QB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has a purple-black seed coat and not sensitive to light. Lasunon et.al., (2022) reported that Nongkhai black jasmine rice possessed total phenolic, total flavonoid and anthocyanin contents in the range of 0.010-0.035 g GAE/100 g, 1.5-3.5 g QE/100 g, and, 0.01-0.03 g/100 g, respectively, which decreased during the cooking process [4]. To our knowledge, the bioactive components and antioxidant activities of Nongkhai black jasmine rice bran oil have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…It has a purple-black seed coat and not sensitive to light. Lasunon et.al., (2022) reported that Nongkhai black jasmine rice possessed total phenolic, total flavonoid and anthocyanin contents in the range of 0.010-0.035 g GAE/100 g, 1.5-3.5 g QE/100 g, and, 0.01-0.03 g/100 g, respectively, which decreased during the cooking process [4]. To our knowledge, the bioactive components and antioxidant activities of Nongkhai black jasmine rice bran oil have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%